DESCRIPTION OF THE KNOWLEDGE OF ADOLESCENT WOMEN CLASS XI ABOUT THE IMPACT OF EARLY MARRIAGE FOR HEALTH IN SENIOR HIGH SCHOOL 2 BAUBAU YEAR 2022 - Swardin, Laode; Wa Ode Nur Syuhada (Rena Cipta Mandiri, 2022)
The rate of early marriage is still very high. Of course, women who marry early will also have many problems. The problems that will be faced, both in terms of physiology, psychology, economy, autonomy, education, and other unfavorable problems. The Indonesian government has enacted laws and regulations to reduce the incidence of early marriage, but in practice there are still many who do early marriage. As in Indonesia, in 2018 the number of women who married before the age of 18 reached 1,220,900 and made Indonesia ranked 10th in the country with the highest child marriage rate in the world. The type of research used is descriptive, which aims to determine the Knowledge Description of Class XI Teenage Girls about the Impact of Early Marriage on Health in SMA Negeri 2 Baubau. The population in this study was 251 people. The number of samples is 71 people. Data analysis was performed using IBM SPSS Statistics Version 22 for a univariate test by looking at, distributing, the proportion or percentage and frequency of knowledge among young women on the impact of early marriage on health. The results showed that from 71 respondents who had good knowledge, 60 respondents (84.5%). Of the 71 respondents who have sufficient knowledge of 9 respondents (12,7%). Of the 71 respondents who have less knowledge of 2 respondents (2.8%). Based on the results of the study, the suggestion that can be put forward is that it is hoped that young women will get used to being active in getting information from anywhere about the negative health impacts that can be caused by early marriage. And it is also expected to improve his attitude towards the impact of early marriage so that it can be in line with his knowledge.